Disposal Practices of Unused Medication Among Pharmacists in Libya - Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and objective. Globally, disposing of unused medicines has become a source of concern, as pharmaceutical waste enters the ecosystem, posing a threat to human health and the environment. This study aimed to assess the disposal practice of unused medication among pharmacists in Libya. This study also seeks to determine if pharmacists plan to have their pharmacies serve as assembly points for potential take-back initiatives. Methods. A random sample of 150 pharmacists from various government and private pharmacies in Tripoli participated in a self-administered questionnaire about their disposal practices, and knowledge on pharmacies serving as collection points for ideal disposal of unused medicines. Descriptive statistics were used to interpret the data. Results. A total of 128 pharmacists completed the survey. The majority of respondents said that throwing discarded drugs in the trash bin was their preferred method of disposal (53.1%), followed by discarding via burn and drug wholesalers (17.2%, 14.8%, respectively). Only 2.1% of the respondents disposed unused medicines according to the WHO guidelines of drug disposal. Moreover, about 65.6% had poor knowledge about Take-Back program. Conclusion. Failure to follow the WHO guidelines for drug disposal raises the risk of contamination of our environment and the likelihood of humans and animals ingesting harmful pharmaceutical wastes.